How tight is the labour market? A micro-based macro indicator - Simen Gaure; Knut Røed (University of Oslo, Department of Economics, 2003)
We develop a new indicator of labour market tightness, based on the pure calendar time changes in individuals' transition rates from unemployment to employment.Based on Norwegian register data from the 1989-2002 period, we show that this indicator,in contrast to the aggregate rate of unemployment, correlates well with an expost-calculated GDP-based business cycle indicator, even around the time of business cycle turning points. The indicator can be calculated just as quickly as the unemployment rate, both at an aggregate and a disaggregate level, and hence improve policy makers ability to assess current labour market developments.
Keywords: C41; E32; J64; 330; Labour market tightness; Business cycles; Unemployment; Arbeitsmarkt; Konjunktur; Arbeitslosigkeit; Norwegen